SYNTHESIS OF ENHANCED [EMIM][DCA] IONIC LIQUID TIO2 MIXED MATRIX MEMBRANES FOR CO2/CH4 SEPARATION - UL MUSTAFA, MUHAMMAD ZIA (2021)
Membrane technology has much potential to be used in CO2-rich offshore applications compared to absorption, adsorption, and cryogenic distillation. However, performance of polymer membranes suffers from Robeson’s upper bound tradeoff between permeability and selectivity. Mixed matrix membrane (MMM) has deficiency due to poor contact between polymer-based matrix and inorganic filler which has resulted in interfacial defects between both materials and agglomeration of the inorganic filler.